Harpoon of the hunter - Markoosie (McGill-Queen's University Press, 1970)
Based on an Inuit legend, Harpoon of the Hunter is a story of life in the old days, not as it appeared to southerners, but as it has survived in the memory of the Inuit themselves. Emerging from a largely oral tradition, it is the first novel by an Inuit written in English. Markoosie has the rare ability to capture the richness and imagery of the Inuit language in English.